Assessing adherence of hospital waste disposal management at Mangochi District Hospital - Buluzi, Mercy Susan (Kamuzu University of Health Sciences, 2022)
Hospital waste management services are aimed at improving health status of hospital workers and also people surrounding the hospital. This study aimed at assessing adherence of hospital waste disposal management processes at Mangochi District Hospital. Questionnaire and Observations were used in the study to collect data. Results from the study is going to help in the adoption of the most efficient method of waste disposal utilization of health services and providing a basis for designing public health measures for Mangochi District Hospital. Needle prick incidences were high due to improper waste disposal management among workers at Mangochi District Hospital. 427people on ART prophylaxis between 2017 and 2019, 127people were due to needle prick incidences by June 2019 representing 29.7% (Prophylaxis hard cover 2017 to 2019). Therefore, this study’s significance was that cleaners acquired knowledge on care to prevent risks and understand the process of waste disposal management, and the managers were reminded to do on job trainings for cleaners. The benefits of proper medical waste management minimized the spread of infections and reduced the risk of accidental injury to staff, patients, visitors and community.